“Dosis de herbicidas pre y post emergentes en arroz (oryza sativa L.) bajo riego con el sistema de labranza mínima en el bajo mayo” - Garcia Pezo, Julio Fausto (2004)
This research on " The dose of herbicides pre and post emergent in rice ( Oryza saliva L)is watered with the system of minimum tilling in Bajo Mayo in the district of Cacatachi". It was developed in a farm that belongs to The National University of San Martín (UN.S.M) which is located in the district ofCacatachi in the province of San Martin, toan altitude of 350 o. s. l., with a rainfall of 1135 mm/year and an average temperature of 25° C. The development took from February to August in 2000. The main objectives pursued were to evaluate the effect and the efficiency of three pre emergent herbicide dose and three post emergent herbicide dose, a witness with manual weeding and with an absolute witness without weeding in the Capirona variety. Oxadiargyl (Raft), a pre emergent herbicide, was used and Carboxipirimidinil (Nominee), a post herbicide emergent, was used, too. A significant difference was found for the yield, standing out T5 (Nominee 0,4 l/ha. with 6510 kg/ha) with the lowest yield T7 (weeding witness) with 5093 kg./ha. ; The "macollamiento" was lower compared to the transplant, reaching averages that vary from 4,6 "macollos' per plant for T2 (Raft 1,0 llha.) to 3,38 "macollos" per plant for T7 ( witness without weeding). The plant height was from 105,48 to 100,38 cm. And the size of the of the corncobvaried from 25,05 to 23,81 cm. Fort these two parameters the averages were less than the ones reported for the same variety with the transplant system with 11 O and 29 cm. respectively. A better control for the three tested types of weeds was observed (Poaceas, cyperaceous and wide lea( ) with the carboxipirimidinil herbicide; However, the group of poaceas are controlled in a more efficient way for the oxadiargyl in its three dose. The performed linear analysis demonstrated an inversely relation among the number of the entire weeds and the yield. Finally, the obtained treatment with the highest relation B/C (1,83) was T8 (witness with manual weeding) followed by pre emergent herbicide treatment in its three doses.